2020
DOI: 10.1021/jasms.0c00059
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Volatile Organic Compounds with Secondary Electrospray Ionization and Proton Transfer Reaction High-Resolution Mass Spectrometry: A Feature Comparison

Abstract: The analysis of volatiles is of high relevance for a wide range of applications from environmental air sampling and security screening to potential medical applications. High-resolution mass spectrometry methods offer a particularly wide compound coverage, sensitivity, and selectivity. Online approaches allow direct analysis in real time without the need for sample preparation. For the first time, we systematically compared the analysis of volatile organic compounds with secondary electrospray ionization (SESI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 27 publications
2
24
0
Order By: Relevance
“…[15] [16] We generated a spectral stitching method by using twenty-two Ion competition particularly suppresses analytes in the higher m/z region -presumably because the ion competition is mainly caused by high abundant low mass matrix compounds. In fact, the ion competition-reduced feature distribution more closely resembles the distribution reported on a SESI-quadrupole time-of-flight (QTOF) instrument [19], where ion competition is not expected because of the ion-trap free nature of a QTOF instrument.…”
Section: Defining the Ion Distribution Of Human Breath And Bacteria Csupporting
confidence: 52%
See 1 more Smart Citation
“…[15] [16] We generated a spectral stitching method by using twenty-two Ion competition particularly suppresses analytes in the higher m/z region -presumably because the ion competition is mainly caused by high abundant low mass matrix compounds. In fact, the ion competition-reduced feature distribution more closely resembles the distribution reported on a SESI-quadrupole time-of-flight (QTOF) instrument [19], where ion competition is not expected because of the ion-trap free nature of a QTOF instrument.…”
Section: Defining the Ion Distribution Of Human Breath And Bacteria Csupporting
confidence: 52%
“…In both polarities the method with 20 m/z windows outperform the full scan method in the higher mass region ( m/z ≥ 200 ), which matches exactly what we expected; that the dominating peaks in the low mass region are saturating the C-trap therefore reduce the overall detection sensitivity ( figure 2 (c)). Reducing the ion competition with the 20 m/z windows results in a similar feature distribution as observed on a SESI-quadrupole time-of-flight (QTOF) instrument [16] , where we assume that ion competition is less pronounced. Therefore, we conclude that a window splitting approach should be considered to make full use of the SESI's high mass ionization capabilities.…”
Section: Defining Ion Distribution Of Human Breath and Bacteria Culturementioning
confidence: 81%
“…SESI-MS has been repeatedly reported as a robust tool for cancer identification based on breath analysis [ 73 , 74 , 75 ]. An interesting study was described by Bruderer et al [ 76 ], who compared the potential of SESI-MS and PTR-MS for VCs analysis in the breath. SESI-MS detected the highest number of compounds in the high mass region ( m / z = 150–250), while PTR-MS was more sensitive in the low mass region ( m / z = 50–150).…”
Section: Real-time Mass Spectrometry Techniquesmentioning
confidence: 99%
“…PTR-MS allowed for the detection of 491 peaks, whilst SESI-MS detected almost double that number (828). Interestingly, only 133 peaks were common for both techniques, and 797 and 374 unique features were detected for SESI and PTR, respectively [ 76 ].…”
Section: Real-time Mass Spectrometry Techniquesmentioning
confidence: 99%
“…Note that PTR‐MS can be also used for quantification at sub‐pptv LOD. Recently it has been compared with SESI‐MS in parallel qualitative analyses, 4 which has shown that the major ions of the analytical mass spectra from both techniques are protonated molecules [M + H] + together with fragments and adducts. However, quantifications were not compared.…”
Section: Figurementioning
confidence: 99%